Multidrug-Resistant Pathogens in Burn Wound, Prevention, Diagnosis, and Therapeutic Approaches (Conventional Antimicrobials and Nanoparticles) - Jaber Hemmati; Mehdi Azizi; Babak Asghari; Mohammad Reza Arabestani (Canadian Journal of Infectious Diseases and Medical Microbiology)
Multidrug-resistant pathogens are one of the common causes of death in burn patients and have a high risk of nosocomial infections, especially pneumonia, urinary tract infections, and cellulitis. The role of prolonged hospitalization and empirical antibiotics administration in developing multidrug-resistant pathogens is undeniable. In the early days of admitting burn patients, Gram-positive bacteria were the dominant isolates with a more sensitive antibiotic pattern. However, the emergence of Gram-negative bacteria that are more resistant later occurs. Trustworthy guideline administration in burn wards is one of the strategies to prevent multidrug-resistant pathogens. Also, a multidisciplinary therapeutic approach is an effective way to avoid antibiotic resistance that involves infectious disease specialists, pharmacists, and burn surgeons. However, the emerging resistance to conventional antimicrobial approaches (such as systemic antibiotic exposure, traditional wound dressing, and topical antibiotic ointments) among burn patients has challenged the treatment of multidrug-resistant infections, and using nanoparticles is a suitable alternative. In this review article, we will discuss different aspects of multidrug-resistant pathogens in burn wounds, emphasizing the full role of these pathogens in burn wounds and discussing the application of nanotechnology in dealing with them. Also, some advances in various types of nanomaterials, including metallic nanoparticles, liposomes, hydrogels, carbon quantum dots, and solid lipid nanoparticles in burn wound healing, will be explained.